C-Fos induces chondrogenic tumor formation in immortalized human mesenchymal progenitor cells. Issue 1 (December 2018) - Abarrategi, Ander; Gambera, Stefano; Alfranca, Arantzazu; Rodriguez-Milla, Miguel; Perez-Tavarez, Raquel; Rouault-Pierre, Kevin; Waclawiczek, Alexander; Chakravarty, Probir; Mulero, Francisca; Trigueros, César; Navarro, Samuel; Bonnet, Dominique; et al.
Abstract Mesenchymal progenitor cells (MPCs) have been hypothesized as cells of origin for sarcomas, and c-Fos transcription factor has been showed to act as an oncogene in bone tumors. In this study, we show c-Fos is present in most sarcomas with chondral phenotype, while multiple other genes are related to c-Fos expression pattern. To further define the role of c-Fos in sarcomagenesis, we expressed it in primary human MPCs (hMPCs), immortalized hMPCs and transformed murine MPCs (mMPCs). In immortalized hMPCs, c-Fos expression generated morphological changes, reduced mobility capacity and impaired adipogenic- and osteogenic-differentiation potentials. Remarkably, immortalized hMPCs or mMPCs expressing c-Fos generated tumors harboring a chondrogenic phenotype and morphology. Thus, here we show that c-Fos protein has a key role in sarcomas and that c-Fos expression in immortalized MPCs yields cell transformation and chondrogenic tumor formation.